PENGUKURAN KUALITAS LAYANAN WEBSITE DUNIAMURAH.COM MENGGUNAKAN METODE WEBQUAL 4.0 PADA PENGGUNA DI WILAYAH JAKARTA - Alif Falih Muhammad Lubis (2023)
Duniamurah website does not include a website that is user friendly because it is not yet compatible with mobile phones or browsers when accessed by customers. Information provided on the website is irrelevant, such as stock information that is not updated and ongoing promo information that has an inaccurate date listed. As well as the payment methods provided by the Duniamurah website are still somewhat out of date because customers have to upload proof of transfer to the website for manual confirmation by the company's administration. webqual 4.0 method. This measurement technique method has 3 main topics, namely usability, information quality, and service interaction quality. By measuring the quality of Duniamurah website services based on user ratings, indicators of recommendations for improving the Duniamurah website will be obtained for companies. The results of this study can provide recommendations for improvement to PT. Putra Perdana Sentosa on the quality of Duniamurah website services based on the main indicators of WebQual 4.0. so that PT. Putra Perdana Sentosa can increase customer satisfaction and make it easier for customers to use the Duniamurah website.